Edukasi dan Pemeriksaan Hemoglobin (Hb) pada Anak Usia Sekolah di Panti Asuhan Sonaf Manekat Kupang, sebagai Upaya Pencegahan Stunting - Aldiana Astuti; Novian Agni Yudhaswara; Agnes Rantesalu; Melani Fernanda Bssie (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Stunting remains a major public health problem in Indonesia, with anemia recognized as an important contributing factor, particularly among school-aged children. The World Health Organization (WHO) identifies anemia as one of the most common nutritional disorders worldwide, while UNICEF highlights its association with impaired growth and increased risk of stunting. However, early detection of subclinical conditions such as borderline hemoglobin (Hb) levels is often neglected, allowing progression to anemia and increasing long-term health risks. This study aimed to integrate health education with Hb screening to improve awareness and identify early anemia risk in a community-based institutional setting. The program combined educational activities with point-of-care Hb assessment using a digital hemoglobinometer. A total of 70 participants were involved, with 42 individuals undergoing Hb screening. The outcomes measured included changes in participants’ knowledge and the distribution of Hb status. Results showed that 11.9% of participants were anemic, consisting of 9.5% with low Hb and 2.4% with very low Hb levels. In addition, 23.8% had borderline Hb levels, indicating a substantial at-risk group. Overall, 35.7% of screened participants exhibited impaired hemoglobin status. Following the intervention, participants demonstrated better understanding of anemia and its relationship with stunting. Individuals identified with anemia or borderline Hb received counseling and referral recommendations. These findings highlight the importance of combining Hb screening with health education to support early prevention of anemia and stunting.